2017
DOI: 10.1155/2017/2637051
|View full text |Cite
|
Sign up to set email alerts
|

Target Organ Damage and the Long Term Effect of Nonadherence to Clinical Practice Guidelines in Patients with Hypertension: A Retrospective Cohort Study

Abstract: Background There was limited published data on target organ damage (TOD) and the effect of nonadherence to practice guidelines in Ethiopia. This study determined TOD and the long term effect of nonadherence to clinical guidelines on hypertensive patients. Methods An open level retrospective cohort study has been employed at cardiac clinic of Gondar university hospital for a mean follow-up period of 78 months. Multivariate Cox regression was conducted to test associating factors of TOD. Results Of the total num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
19
1
1
Order By: Relevance
“…Inability to consume drugs of antihypertension has been a factor associated with the incidence of cardiovascular complications in patients with hypertension in this study. The results of this study are consistent with the results of the study of Abegaz et al (2017) who found that the right treatment tends to develop target organ damage (TOD) which is very slow, meaning that non-compliance in taking antihypertensive drugs will accelerate damage to target organs or target organs demage in patients with hypertension. Researchers found that non-compliance with the consumption of drugs of anti-hypertension is caused by patients feeling no complaints, forgetting, and busy with daily activities.…”
Section: Methodssupporting
confidence: 90%
“…Inability to consume drugs of antihypertension has been a factor associated with the incidence of cardiovascular complications in patients with hypertension in this study. The results of this study are consistent with the results of the study of Abegaz et al (2017) who found that the right treatment tends to develop target organ damage (TOD) which is very slow, meaning that non-compliance in taking antihypertensive drugs will accelerate damage to target organs or target organs demage in patients with hypertension. Researchers found that non-compliance with the consumption of drugs of anti-hypertension is caused by patients feeling no complaints, forgetting, and busy with daily activities.…”
Section: Methodssupporting
confidence: 90%
“…Other studies have found large differences in the proportion of LVH among hypertensive patients across age, gender, duration of hypertension, and geographic location, with rates ranging from 2% in Ethiopia [6], 23% in Spain [15] and 28% in Nigeria [16] to as high as 33% in Greece [7]. Similarly, the rates of hypertension-related HF vary considerably across populations.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence was modeled with DisMod-MR 2.1, a Bayesian meta-regression tool developed specifically for the GBD study that ensures consistency of epidemiological parameters for the conditions studied [10,12]. A range of additional analytical techniques were applied to correct for biases and inconsistencies in the data, as described in the GBD publica-tions [6][7][8][9][10][11][12]. DALYs were calculated as the sum of years of life lost due to premature mortality and years lived with disability (a measure of non-fatal health loss); hence DALY, as a measure of overall disease burden, expresses lost years of healthy life [12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations